Enhancement in microwave absorption properties by adjusting the sintering conditions and carbon shell thickness of Ni@C submicrospheres. Issue 4 (7th January 2022) - Shen, Xun; Yang, Shu-Hao; Yin, Peng-Gang; Li, Chao-Qin; Ye, Jin-Rui; Wang, Guang-Sheng
Abstract : The core–shell Ni@C submicrospheres were fabricated by sintering method and combined with PVDF to prepare Ni@C/PVDF composite, which possessed optimal wave absorption property with RL min of −71.32 dB and EAB of 5.62 GHz at 1.95 mm. Abstract : The combination of traditional magnetic metal materials and dielectric carbon materials to improve microwave absorption properties has generated great interest. In this work, Ni@C submicrospheres were successfully synthesized by sintering the Ni@RF precursor and were compounded with a polymer matrix PVDF because of their excellent dielectric and mechanical properties. The outstanding microwave absorption performance was obtained by adjusting the sintering conditions and carbon shell thickness to achieve good impedance matching and high attenuation capability. It was found that the Ni@C/PVDF composite (850 °C, 3 h, d (carbon) = 64.3 nm) shows excellent microwave absorption performance with a strong absorption value of −71.32 dB at 14.04 GHz, a broad bandwidth of 5.62 GHz and a thin matched the thickness of 1.95 mm. These findings provide a method for designing high-performance microwave absorption materials.